Identifikasi Limbah Elektronik dan Keluhan Subyektif Kesehatan pada Pengepul di Kecamatan Pamulang, Kota Tangerang Selatan, Indonesia - Rahma Belinda Alifa; Budiyono Budiyono; Dewanti Nikie Astorina Yunita (Fakultas Kesehatan Masyarakat Universitas Andalas, 2022)
Electronic waste (e-waste) contains various hazardous materials and affects human health, especially collectors, is increasing worldwide and in Indonesia. This study aims to identify the types of e-waste collected and the potential health problems for collectors in Pamulang district. This is a descriptive study with cross-sectional approach. The accessible population was collectors encountered during the study. The sample size in this study was 10 respondents obtained by non-random method, by accident followed by snowballing. The instruments used are validated and reliable questionnaires, observation sheet, and GPS that reveal study objectives. The analysis was performed by using a frequency distribution to explain e-waste and subjective health problems. E-waste found (in units) were 286 lamps, 53 temperature exchange equipment such as air conditioner, 98 screens, monitors, and equipment containing screens having a surface greater than 100 cm2 such as television, 202 small IT and telecommunications equipment such as smartphones, 194 small equipment such as rice cookers, and 79 large equipment such as washing machines. Collectors receive 5 kgs - 8 tons e-waste weekly. Subjective health problems experienced include low back pain and metal fume fever symptoms, such as lethargy, muscle aches, sweating, and headaches. It can be concluded that the e-waste found in collectors dominated by the lamp category, and subjective health problems that are often found in collectors are symptoms of metal fume fever. Collectors who experience it can rest and treat symptoms that arise. Further research is needed to ascertain the link between health problems and e-waste.